Is exposure to poultry harmful to child nutrition?: An observational analysis for rural Ethiopia - Headey, Derek D.; Hirvonen, Kalle (Public Library of Science, 2016)
Although strategic thinking on water, sanitation and hygiene (WASH) has prioritized reducing exposure to human feces in order to limit diarrheal infections, recent research suggests that elevated exposure to livestock–particularly poultry and poultry feces–may be an important risk factor for diarrhea, environmental enteric disorder (EED) and respiratory infections, all of which may seriously retard linear growth in young children. Yet a very different literature on nutrition-sensitive agriculture suggests that livestock ownership is highly beneficial for child growth outcomes through its importance for increasing consumption of nutrient-rich animal sourced foods, such as eggs. Together, these two literatures suggest that the net nutritional benefit of poultry ownership is particularly ambiguous and potentially mediated by whether or not children are highly exposed to poultry. We test this novel hypothesis using a large agricultural survey of rural Ethiopian households that includes measures of child height-for-age Z-scores (HAZ), ownership of poultry and other types of livestock, and an indicator of whether livestock are kept within the main household dwelling overnight. We used least squares regression analysis to estimate unadjusted and adjusted models that control for a wide range of potentially confounding factors. We find that while poultry ownership is positively associated with child HAZ [β = 0.291, s.e. = 0.094], the practice of corralling poultry in the household dwelling overnight is negatively associated with HAZ [β = -0.250, s.e. = 0.118]. Moreover, we find no negative associations between HAZ and corralling other livestock species indoors. These results suggest that while poultry ownership can be beneficial to child growth, overly close exposure to poultry poses a concurrent risk factor for undernutrition, most likely because of increased risk of infection.